Great Northern Iron Ore Properties - Jacob, Joshy, (SAGE Knowledge. Cases., 2017)
The shares of Great Northern Iron Ore Properties (GNIOP) closed at $72.6 on the NYSE on the ex-dividend date of September 26, 2013. At the ex-dividend price, GNIOP was trading at a trailing P/E ratio of 7.35 (calculated using the annualized earnings of the 9-months ended on September 30, 2013 and the closing price of $72.6) and was quoting an annualized dividend yield of about 14%. Several analysts identified it among the top-10 dividend yield stocks at that time. For instance, The Street identified it among the top-3 buy rated dividend stocks.However, according to some market analysts, GNIOP was greatly overpriced. They pointed out that GNIOP, incorporated as a trust, was set to expire on April 6, 2015, following which its shares would be delisted from the NYSE. The expiry limited the potential of shareholder cashflows to just six quarters of dividends and a final liquidating payment.